Access to Land in Rural India - Mearns, Robin (The World Bank, 1999)
May 1999 - Access to land is deeply important in rural India, where the incidence of poverty is highly correlated with lack of access to land. The author provides a framework for assessing alternative approaches to improving access to land by India's rural poor. He considers India's record implementing land reform and identifies an approach that includes incremental reforms in public land administration to reduce transaction costs in land markets (thereby facilitating land transfers) and to increase transparency, making information accessible to the public to ensure that socially excluded groups benefit. Reducing constraints on access to land for the rural poor and socially excluded requires five key issues: restrictions on land-lease markets, the fragmentation of holdings, the widespread failure to translate women's legal rights into practice, poor access to (and encroachment on) the commons, and high transaction costs for land transfers. Among guidelines for policy reform the author suggests: -Selectively deregulate land-lease (rental) markets, because rental markets may be important in giving the poor access to land. -Reduce transaction costs in land markets, including both official costs and informal costs (such as bribes to expedite transactions), partly by improving systems for land registration and management of land records. -Critically reassess land administration agencies and find ways to improve incentive structures, to reduce rent-seeking and base promotions on performance. -Promote women's independent land rights through policy measures to increase women's bargaining power within the household and in society generally. -Improve transparency of land administration and public access to information, to reduce rent-seeking by land administration officers and to strengthen poor people's land rights (and knowledge thereof).